2015
DOI: 10.1007/s00289-015-1580-4
|View full text |Cite
|
Sign up to set email alerts
|

Plasticization of amorphous polystyrene by volatile organic compounds

Abstract: International audienceThe plasticizing effect of 4 model volatile compounds (n-hexane, toluene, p-xylene, and ethylbenzene), able to be sorbed on polystyrene (PS) was studied. A large weight fraction range was investigated (up to 0.35) using differential scanning calorimetry. Mathematical modeling, using Fox, Kelly-Bueche, Chow and Gordon-Taylor models, was performed to model the behavior of the glass transition temperature of PS after VOC sorption. A strong plasticization of PS was evidenced by a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The inset of Figure shows the predicted dynamic glass transition temperature defined by τ hop , PS = 100 s and compares it to the experimental DSC measurements . The theory curve captures well the large ∼120 K reduction of the glass transition temperature as toluene loading reaches about 30%.…”
Section: Diffusion In a Polymer–molecule Mixturementioning
confidence: 68%
See 1 more Smart Citation
“…The inset of Figure shows the predicted dynamic glass transition temperature defined by τ hop , PS = 100 s and compares it to the experimental DSC measurements . The theory curve captures well the large ∼120 K reduction of the glass transition temperature as toluene loading reaches about 30%.…”
Section: Diffusion In a Polymer–molecule Mixturementioning
confidence: 68%
“…Toluene self-diffusion constant (in unit of cm 2 /s) in a molten polystyrene matrix as a function of toluene weight fraction predicted by SCCHT (curves) and measured in experiment (symbols) at 383 and 413 K. Inset: Polystyrene glass transition temperature (in Kelvin) as a function of toluene weight fraction predicted by SCCHT (curve) and measured by DSC experiment (symbols). Dashed curves throughout the figure represent theoretical results in the no-adjustable-parameter version of the calculation discussed in the text.…”
Section: Diffusion In a Polymer–molecule Mixturementioning
confidence: 99%
“…We can assume that the BCPs start to vitrify at the Φ p value where the glass transition temperature ( T g ) of PS chains in toluene reaches the temperature of the system (30 °C). Therefore, we used the Fox equation for PS and toluene to find the Φ p of PS that yields a T g = 30 °C as where the T g , p of neat PS (373 K) and T g , s of toluene (137.5 K) were used to calculate the weight fraction of polymer ( w p ), which yielded the volume fraction Φ p of 0.842 . The D o of toluene at 30 °C was estimated to be 10 –8 cm 2 /s from the literature .…”
Section: Resultsmentioning
confidence: 99%
“…This could cause additional emission of VOCs from GTR. It should be also pointed out that formed VOCs could act like plasticizers [41], while their interactions with polymeric matrix could affect the results of SHS-GC-MS. Furthermore, it was observed that volatile organic compounds were omitted directly to the environment after MW treatment of GTR, which also affected the total content of VOCs in studied samples.…”
Section: Resultsmentioning
confidence: 99%